The discovery of sofosbuvir: a revolution for therapy of chronic hepatitis C. (2nd December 2015) - Gentile, Ivan; Maraolo, Alberto Enrico; Buonomo, Antonio Riccardo; Zappulo, Emanuela; Borgia, Guglielmo
Abstract : Introduction: Hepatitis C virus (HCV) infection is a worldwide health problem, whose management has been revolutionized after the availability of sofosbuvir, a direct-acting antiviral (DAAs). Sofosbuvir is a HCV NS5B polymerase inhibitor. Antiviral regimens including sofosbuvir are associated with success rates >90%, even in the case of "difficult-to-treat" patients such as subjects with liver cirrhosis as well as prior null response to IFN and ribavirin. Areas covered: This drug discovery case history focuses on the pre-clinical and clinical development of sofosbuvir. The authors analyze all of the main steps leading to the global approval of sofosbuvir. The paper also highlights the encouraging data from the subsequent trials wherein sofosbuvir was tested in combination with other DAAs (IFN- and often ribavirin-free regimens) and from first real life studies. Expert opinion: Sofosbuvir is a very powerful weapon in the new armamentarium against HCV. Thanks to its valuable features including its pangenotypic activity, once-daily oral administration, its excellent tolerability, and safety profile, it represents the backbone of several effective regimens, in combination with IFN or with other DAAs (IFN-free therapies). Regimens including sofosbuvir have quickly become the touchstone for all the novel anti-HCV treatments.